3D hierarchical flower-like NiMoO4@Ni3S2 composites on Ni foam for high-performance battery-type supercapacitors. (January 2021) - Feng, Lina; Yang, Ping; Ling, Wenqin; Wang, Shaohua; Shi, Jianjun; Wang, Fengwu
Abstract: A hydrothermal method was used to prepare a hierarchical flower-like NiMoO4 @Ni3 S2 composite on a three-dimensional Ni foam substrate, and the effects of different amounts of ethylene glycol in the precursor solution on the morphology and performance of Ni@NiMoO4 @Ni3 S2 were investigated. The as-synthesized No-10/Ni3 S2 electrode exhibits a specific capacity up to 870 C g −1 at 0.6 A g −1 and excellent cycle stability (capacity retention of 81.2% after 8000 cycles). More importantly, in a hybrid supercapacitor with a No-10/Ni3 S2 as a positive electrode and activated carbon (AC) as a negative electrode (No-10/Ni3 S2 //AC), the energy density of 128.31 W h kg −1 at a power density of 7106.4 W kg −1 . As displayed, the performances make No-10/Ni3 S2 a promising candidate as high-performance electrode material for supercapacitors. Highlights: The morphology of NiMoO 4 on Ni foam was affected greatly by the amount of ethylene glycol. The as-prepared flower-like electrode material exhibits high performance in supercapacitors. The assembled ASC achieved specific energy of 90.9 W h kg −1 at a specific power of 218 W kg −1 . A LED (3.0 V, 320 mA) was lighted up for 45 min by two ASCs assembled in series.